Board Characteristics and Firm Performance: Evidence from Indonesia - Hidayat, Athalia Ariati; Utama, Sidharta (International Research Journal of Business Studies, 2015)
This research examines the effect of board characteristics (comprising in different sized proportions: family commissioners, family directors, independent commissioners, ex-government officer commissioners, and board of commissioners size) to firm performance. Using fixedeffects data panel regression, this research investigates 293 firms listed on the Indonesian Stock Exchange during 2008-2012. Firm performance is proxied by market measure (Tobin’s Q) and accounting measure (ROA). The findings of this research suggest that the proportion of family commissioners and family directors have positive impact only to Tobin’s Q value, while the proportion of independent directors can increase both Tobin’s Q and ROA. On the other hand, this research finds that the proportion of ex-government officers in the board gives no impact to firm performance. This research also finds that the board size has U-shaped non-linear relationship with firm performance as proxied by Tobin’s Q and ROA.